Traditional Chinese Medicine for Postoperative Care following Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-Analysis. (21st September 2021) - Chang, Hokyung; Kim, Hyungsuk; Kim, Koh-Woon; Cho, Jae-Heung; Song, Mi-Yeon; Chung, Won-Seok
Abstract : Objectives . This review verifies the clinical effects of traditional Chinese medicine (TCM) combined with conventional rehabilitation after anterior cruciate ligament reconstruction (ACLR). Methods . MEDLINE/PubMed, EMBASE, CENTRAL, JMAS, CNKI, and seven Korean databases were searched using predetermined strategies. The risk of bias was assessed using Cochrane Collaboration's tool and a meta-analysis was conducted accordingly. Results . Nineteen randomized controlled trials involving 1283 participants were included in this systematic review and meta-analysis. The TCM treatment group showed more significant improvements in pain (MD −0.74, 95% CI [−0.93, −0.54]; I2 = 89%), range of motion (ROM) (SMD 1.19, 95% CI [0.78, 1.59]; I2 = 78%), and knee swelling (SMD −1.72, 95% CI [−2.38, −1.07]; I2 = 76%). The Lysholm score of the TCM treatment group significantly improved (MD 5.62, 95% CI [3.93, 7.32]; I2 = 84%) relative to the control group. The IKDC subjective score (MD 3.40, 95% CI [−0.61, 7.41]; I2 = 97%) and the hospital for special surgery (HSS) score did not improve initially (MD 6.79, 95% CI [−1.27, 14.86]; I2 = 97%) but did so during the subgroup analysis. TCM showed a long-term effect on the IKDC subjective score (MD −0.51, 95% CI [−1.69, 0.67]; I2 = 30%). A longer treatment period of 12 weeks showed more improvement (MD 5.96, 95% CI [0.69, 11.22]; I2 95%). Conclusion . TCM can be used as an adjuvant therapy to conventional rehabilitation for relieving pain, improving ROM and oedema, and facilitating better function of the knee joint after ACLR. However, this recommendation should be cautiously applied in clinical practice owing to the low quality of the included studies.